Qualitative Study of Community Participation Behavior in the Family Planning Program at the Kajuara Community Health Center, Bone District, South Sulawesi, Indonesia - Mustika Eka Pratama Musakkar; Erniati Erniati; Arlin Adam; Andi Alim (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The high birth rate is the main reason for the need for family planning services. Many women experience difficulties in determining the choice of type of contraception. This is not only because of the limited available methods but also because of their ignorance to make the right choice according to age, number of children and the side effects that often arise. This study aimed to obtain in-depth information about the behavior of community participation in the family planning program at the Kajuara Community Health Center, Bone Regency. Subjects and Method: The type of research used is descriptive qualitative research. The number of informants in this study was 7 people. The variables of this study are people's behavior, knowledge, attitudes, and actions. These research variables in a qualitative approach are referred to as the research focus. Data collection was done through in-depth interviews. Data analysis using